Mechanical damage characterization in human femoropopliteal arteries of different ages. (May 2019) - Anttila, Eric; Balzani, Daniel; Desyatova, Anastasia; Deegan, Paul; MacTaggart, Jason; Kamenskiy, Alexey
Graphical abstract: Abstract: Endovascular treatment of Peripheral Arterial Disease (PAD) is notorious for high failure rates, and interaction between the arterial wall and the repair devices plays a significant role. Computational modeling can help improve clinical outcomes of these interventions, but it requires accurate inputs of elastic and damage characteristics of the femoropopliteal artery (FPA) which are currently not available. Fresh human FPAs from n = 104 tissue donors 14–80 years old were tested using planar biaxial extension to capture elastic and damage characteristics. Damage initiation stretches and stresses were determined for both longitudinal and circumferential directions, and their correlations with age and risk factors were assessed. Two and four-fiber-family invariant-based constitutive models augmented with damage functions were used to describe stress softening with accumulating damage. In FPAs younger than 50 years, damage began accumulating after 1.51 ± 0.13 and 1.49 ± 0.11 stretch, or 196 ± 110 kPa and 239 ± 79 kPa Cauchy stress in the longitudinal and circumferential directions, respectively. In FPAs older than 50 years, damage initiation stretches and stresses decreased to 1.27 ± 0.09 (106 ± 52 kPa) and 1.26 ± 0.09 (104 ± 59 kPa), respectively. Damage manifested primarily as tears at the internal and external elastic laminae and within the tunica media layer. Higher body mass index and presence of diabetes were associated with lower damage initiation stretches and higher stresses. The selected constitutive models were able to accurately portray the FPA behavior in both elastic and inelastic domains, and properties were derived for six age groups. Presented data can help improve fidelity of computational models simulating endovascular PAD repairs that involve arterial damage. Statement of significance: This manuscript describes inelastic, i.e. damage, behavior of human femoropopliteal arteries, and provides values for three constitutive models simulating this behavior computationally. Using a set of 104 human FPAs 14–80 years old, we have investigated stress and stretch levels corresponding to damage initiation, and have studied how these damage characteristics change across different age groups. Presented inelastic arterial characteristics are important for computational simulations modeling balloon angioplasty and stenting of peripheral arterial disease lesions.